Human Skin WoundWelding Using 980 nm Diode Laser: an in Vitro Experimental Study - Abbood, Ahmed A. (Iraqi Journal of Laser, 2019)
Laser assisted skin wound closure offers many distinct advantages over conventional closuretechniques. The objective of this in vitro experimental study, carried out at the Institute of Laser forPostgraduate Studies/Baghdad University, was to determine the effectiveness of 980 nm diode laser inwelding of human skin wounds. Multiple 3-4 cm long full thickness incisions in a specimen of humanskin obtained from the discarded panniculus of an Abdominoplasty operation were tried to be laserwelded using a 4 mm spot diameter laser beam from a 980 nm diode laser at different laser parametersand modes of action. The tensile strength at the weld site was analyzed experimentally. Although laserassisted wound welding did actually happen at many laser parameter settings, it was not strong enough tobe clinically useful in living human beings. Despite the 980-nm diode laser system has proved to be aneffective way of wound welding but it the weld was of low tensile strength to withstand living patientnormal daily activity and movement. It can really shorten the operative time required to close a wound ifproper laser parameters were used among an endless effective combinations of parameters. Further futurestudies are highly recommended on live human beings